Pembinaan Olimpiade Sains Nasional Informatika di SMAN 2 dan SMAN 1 Jember - Atmoko, Rizky Alfanio; Saputra, Muhammad Andryan Wahyu; Novtahaning, Damar; Kartiko, Erik Yohan; Ranggianto, Narandha Arya; Segara, Akbar Pandu; Arief, M. Habibullah (Universitas Jember, 2025)
Program